Efeitos do aspartame e do orlistate em animais saudáveis e com doença gordurosa do fígado associada a disfunção metabólica: parâmetros bioquímicos, metabólicos e oxidativos - Bressan, Caroline Azzolin (2023)
This thesis evaluated the effects of chronic administration of aspartame (ASP), as well as investigated the effects of ASP, orlistat, and their association in the liver of healthy mice and mice with metabolicassociated fatty liver disease (MAFLD). For this, two experiments were carried out. In experiment I, Swiss mice received 0.9% NaCl or ASP (80 mg/kg) for 12 weeks. In this experiment, oxidative and inflammatory parameters associated with fibrosis progression were evaluated. The results showed that the administration of ASP led to liver damage and increased aminotransferase activities. ASP also caused liver fibrosis, evidenced by histological analysis and upregulation of pro-fibrotic factors (Tgfb1, Col1a1, and Acta2). In addition, it caused a decrease in the activation of nuclear erythroid factor 2- related factor 2 (Nrf2), thus decreasing the activity of antioxidant enzymes, and causing an increase in lipid peroxidation, which probably triggered the activation of the NLRP3 inflammasome and the induction of p53. ASP also caused a decrease in the coactivator 1α of peroxisome proliferator-activated receptor gamma (PGC-1α) levels, possibly by the p53 activation. Moreover, it induced a worsening in the lipid profile, accumulation of lipids in the liver, and the impairment of gluconeogenesis, evidenced by the downregulation of its enzymes, and consequent hypoglycemia. Experiment II consisted of a period of MAFLD induction (8 weeks) in C57BL/6 mice through a Western-type diet (WD), followed by a period of treatment with ASP (80 mg/kg) and/or orlistat (100 mg/kg of diet) (6 weeks), totaling 14 weeks of experiment. Biochemical, histological, oxidative stress, and glutathione (GSH) metabolism parameters were analyzed. It was observed that WD led to an increase in body weight and adiposity, as well as hyperglycemia, hypercholesterolemia, hepatic steatosis, increased activity of aminotransferases, and accumulation of lipids in the liver. In addition, it caused an increase in lipid peroxidation and hydrogen peroxide levels and a decrease in antioxidant defenses. Consumption of ASP by healthy subjects or those with MAFLD resulted in hyperglycemia, GSH system impairment, and liver damage. In mice with MAFLD treated with orlistat, an improvement in body weight, adiposity, liver function, oxidative parameters, and antioxidant defenses was observed, while healthy animals showed hyperglycemia, hypertriglyceridemia, and increased aspartate aminotransferase activity. The association of ASP and orlistat in healthy mice led to weight loss and a decrease in adiposity, but also caused hyperglycemia, hypercholesterolemia, and increased activity of alanine aminotransferase. In contrast, in mice with MAFLD there was a decrease in body weight, adiposity, and in fasting glucose, as well as a reduction of oxidative stress biomarkers, improvement of hepatic function and an increase in the antioxidant defenses. In conclusion, ASP has toxicity when ingested by healthy individuals, but when associated with orlistat and consumed by individuals with MAFLD, it seems beneficial. However, it is necessary to continue the studies started in this thesis in order to better understand the mechanisms involved in the observed effects.